Public Attention to Gender Equality and Board Gender Diversity (Texas Journal of Multidisciplinary Studies, 2023)
Public attention to gender equality and board gender diversity has become a prominent issue in recent years. With the rise of social movements and increased awareness of systemic inequalities, individuals and organizations are placing a greater emphasis on achieving gender balance in corporate leadership positions. This shift in public attention has sparked important discussions and initiatives aimed at creating more diverse and inclusive boardrooms.